ÜÇ DEVİR, ÜÇ HAMDİ EFENDİ - (:unkn) unknown (My University, 2015)
Elmalılı Hamdi Efendi ve çağdaşı birçok âlim, aydın farklı özelliklere ve arayışlara sahip üç ayrı dönemi yaşamış olmak bakımından istisnai denebilecek bir örneklik ortaya koyarlar. Çocuklukları, tahsilleri ve ilk görevleri Sultan Abdülhamit zamanında, siyasî mücadeleleri ve ilk ürünlerini vermeleri, belki tanınır bir isim olarak ortaya çıkışları II. Meşrutiyet devrinde, yetişkinlik çağları ve büyük eserlerini vermeleri ise Cumhuriyet devrinde oldu. Bu üç devir onların fikirleri, anlayış ve arayışları, yaşama tarzları, hatta inançları üzerinde de etkili oldu. Bu çalışma Elmalılı Hamdi Efendi örneği üzerinden bu üç dönemi ve özelliklerini, kuvvet ve zaaflarıyla ele almayı denemektedir.

Elmalili Hamdi Efendi and his contemporary many scholars, intellectuals lived in three different periods with respect to different properties and quests and they reveal a sample which can be called exceptional. Their childhoods, educations and first tasks were in the period of Abdulhamid II. Their political struggles, their first works and their appearances as famous people were in the Second Constitutionalism Period. Also, their adulthood periods and their great works were in the Republic Period. These three periods influenced on their thoughts, understandings, searchings, lifestyles and even beliefs. This article has been trying to deal with these three periods and their characteristics with their strengths and weaknesses on sample of Elmalili Hamdi Efendi.
THREE PERIODS AND THREE HAMDI EFEND
Keywords: Din Bilimi